LINE application: An alternative tool to develop writing abilities - Jumariati Jumariati; Emma Rosana Febriyanti (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
This study tried to reveal the potential use of LINE application in developing students’ writing abilities through blended learning. It employed a quasi-experimental design which involved thirty-nine students of the advanced writing course. The experimental group was taught by using process and product approach combined with LINE application with teacher’s and classmates’ feedbacks while the control group was taught by using a conventional method without LINE application. The data were the result of students’ writings collected by using a writing test and scoring rubric as the instruments. The analysis of the students’ scores was carried out by employing the independent sample t-test. The finding showed that there was a significant effect of the use of LINE application on the students’ writing abilities. Furthermore, the differences were found in the components of vocabulary, grammar, organization, content, and mechanics. The study concluded that LINE application was a potential tool to develop students’ abilities in writing provided that it was combined with teachers’ and classmates’ feedback which facilitated students’ writing improvement.